Social-political context at the basis of adopting current regulations regarding preventive measures in the criminal process - Stanciu, Mihai-Alexandru (Technium Social Sciences Journal, 2021)
In order for the criminal proceedings to run normally and to achieve its purpose, there may be a need to use means of coercion against the defendant, to prevent him from obstructing the prosecution or the proceedings subsequent to his prosecution or even to prevent him. to commit other crimes. This role belongs to the preventive measures aimed to ensure the proper conduct of the criminal proceedings, to prevent the suspect or defendant from evading criminal prosecution or trial or to prevent the commission of another crime. However, preventive measures may be disposed only under the conditions expressly provided by law and only when they are proportionate to the seriousness of the charge against the person against whom they are taken and are necessary to achieve the purpose pursued by their disposition.